The bulky N(6) substituent of cabergoline is responsible for agonism of this drug at 5-hydroxytryptamine (5-HT)2A and 5-HT2B receptors and thus is a determinant of valvular heart disease - Kekewska, Alexandra; Hübner, Harald; Gmeiner, Peter; Pertz, Heinz H. (Journal of Pharmacology and Experimental Therapeutics, 2011)
Fibrotic valvular heart disease (VHD) has been observed in patients with Parkinson's disease treated with dopamine receptor agonists such as pergolide and cabergoline. 5-Hydroxytryptamine receptor (5-HT R) agonism is the most likely cause, but other 5-HT receptors may also play a role in VHD. We aimed at characterizing the molecular fragment of cabergoline responsible for agonism at 5-HT R and 5-HT R. Cabergoline with an allyl substituent at N(6) behaved as a potent 5-HT R full agonist in relaxation of porcine pulmonary arteries and as a weaker 5-HT R partial agonist in contraction of coronary arteries. The same was true for cabergoline derivatives with cyclopropylmethyl, propyl, or ethyl at N(6). However, agonism was converted into antagonism, when the N(6) substituent was methyl. 6-Methylcabergoline retained agonism compared with cabergoline at human dopamine D and human dopamine D receptors as determined by guanosine 5′-O-(3-[ S]thio) triphosphate binding. In porcine aortic valve cusps, 5-HT-induced contractions were inhibited by ketanserin (5-HT R antagonist) but not by N-(1-methyl-1H-5-indolyl)-N′-(3-methyl-5- isothiazolyl)urea (SB204741) (5-HT R antagonist). In porcine valvular interstitial cells, cabergoline-induced activation of extracellular signal-regulated kinase (ERK) 1/2, an initiator of cellular proliferation and activity, was blocked by (R)-(+)-4-(1-hydroxy-1-(2,3-dimethoxyphenyl)methy1)-N- 2-(4-fluorophenylethyl)piperidine MDL100907) (5-HT R antagonist) and N-[4-methoxy-3-(4-methyl-1-piperazinyl)phenyl]-2′-methyl-4′-(5- methyl-1,2,4-oxadiazol-3-yl)-1,1′-biphenyl-4-carboxamide (GR127935) (5-HT R antagonist), whereas the stimulatory effect on [ H]proline and [ H]glucosamine incorporations (indices of extracellular matrix collagen and glycosaminoglycan) was blocked by MDL100907. We conclude that the bulky N(6) substituent of cabergoline is responsible for 5-HT R and 5-HT R agonism. The increased ERK1/2 phosphorylation and production of extracellular matrix by cabergoline are mediated by 5-HT Rs. However, the moderate potency of cabergoline at native 5-HT Rs suggests that these are not the preferential target in VHD in vivo. Copyright © 2011 by The American Society for Pharmacology and Experimental Therapeutics.